2007
DOI: 10.1210/jc.2007-0849
|View full text |Cite
|
Sign up to set email alerts
|

Replication and Identification of Novel Variants at TCF7L2 Associated with Type 2 Diabetes in Hong Kong Chinese

Abstract: Our results are consistent with others' findings that variations at TCF7L2 contribute to T2D, including Chinese. The presence of association signals spanning several LD blocks warrants further examination of extended regions to reveal the causal variant(s) for this important T2D gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 28 publications
5
85
2
Order By: Relevance
“…This is in keeping with the prevailing view that abnormalities in ␤-cell function play a critical role in defining the risk and development of type 2 diabetes in different populations (34 (Table 4). Our previous work and that of others suggest the presence of additional risk loci at TCF7L2 for type 2 diabetes in Chinese compared with Europeans (35,36). Given the differences in linkage disequilibrium pattern and risk allele frequencies, it will be valuable to further examine these genes thoroughly to search for population-specific and/or shared culprit disease loci and the associated phenotypes in different ethnic groups.…”
Section: Discussionmentioning
confidence: 88%
“…This is in keeping with the prevailing view that abnormalities in ␤-cell function play a critical role in defining the risk and development of type 2 diabetes in different populations (34 (Table 4). Our previous work and that of others suggest the presence of additional risk loci at TCF7L2 for type 2 diabetes in Chinese compared with Europeans (35,36). Given the differences in linkage disequilibrium pattern and risk allele frequencies, it will be valuable to further examine these genes thoroughly to search for population-specific and/or shared culprit disease loci and the associated phenotypes in different ethnic groups.…”
Section: Discussionmentioning
confidence: 88%
“…Hayashi et al (2007) replicated the association of TCF7L2 with type 2 diabetes in Japanese. Contradictory results were reported for Han Chinese populations (Ng et al 2007;Chang et al 2007), but these two reports found that other common SNPs (rs11196218 and rs290487, respectively) were associated with type 2 diabetes. This apparent difference between Asian populations could be due to the relatively small sample sizes involved.…”
Section: Introductionmentioning
confidence: 79%
“…Despite increasing evidence that the TCF7L2 gene is associated with an increased T2DM risk in ethnic groups worldwide (Hayashi et al, 2007;Miyake et al, 2008;Palizban et al, 2012;Uma Jyothi et al, 2013;Wang et al, 2013), some studies presented the opposite conclusion (Chang et al, 2007;Ng et al, 2007;Zheng et al, 2012a). No consistent results have been reported because of the limited sample size and ethnicity heterogeneity in the studies.…”
Section: Discussionmentioning
confidence: 94%